Impaired attentional bias toward one's own face in autism spectrum disorder: ERP evidence. Issue 2 (1st December 2021) - Cygan, Hanna B.; Nowicka, Maria M.; Nowicka, Anna
Abstract: Converging lines of evidence seem to indicate reduced self‐referential processing in individuals with autism spectrum disorder (ASD). However, processing of one's own face has rarely been investigated in the context of ASD. Thus, the aim of the present study was to elucidate the role of attentional biases in the processing of self‐ and other faces in ASD. To achieve this goal we presented participants with images of their own face, the face of a close‐other, and famous and unknown faces in a Stroop‐like paradigm. Participants (22 with ASD, 22 typically developing [TD]) were instructed to indicate the color of presented faces while EEG was recorded. Our event‐related potential results clearly showed that self‐face was associated with larger P3 amplitudes than all other faces in the TD group, thus indicating a strong attentional bias toward one's own face. In the ASD group, P3 to the self‐face and the close‐other's face did not differ, suggesting similar attentional biases in both cases. In line with these P3 findings, nonparametric cluster‐based permutation tests showed an analogous pattern of results: significant clusters for the self‐face compared with all other faces in the TD group, and no significant cluster in the ASD group. Overall, our findings revealed impaired attentional bias to one's own face and diminished self versus other differentiation in individuals with ASD. The similar neural underpinnings of the self‐face and other faces supports previous findings indicating reduced self‐prioritization among individuals with ASD.